Investing in real estate - Eldred, Gary W. (Hoboken, New Jersey : John Wiley & Sons, Inc., 2012)
'To explore and illustrate contemporary and evolving market conditions and investment opportunities, this newly revised edition will include the following: 1. Provide historical/cyclical context to emphasize the unprecedented combination of bargain pricing and near record low interest rates now available in most cities. 2. Show how to meet and exceed today's changed loan underwriting standards. (Yes, loans are widely available-but readers/would-be investors must learn how to navigate the maze). 3. Discuss effective ways to successfully negotiate below-market prices with banks, distressed owners/mortgagors, and government agencies (HUD, FHA, Fannie, Freddie, etc.) 4. Reveal methods that will make sure your appraisal comes in at the value you want/need for loan approval. 5. Explain how to legally and ethically use easier/low down payment, owner-occupied financing to acquire investment properties. 6. Guide readers through the new procedures and processes used to acquire REOs (relatively) quickly and on favorable terms as well as illustrate how to structure and complete short sales on favorable terms.7. How to find motivated sellers and/or market properties through social media. 8. Capitalize on the low CD rate environment to persuade sellers to offer OWC property financing-indeed, a large and growing number of sellers need no persuasion. OWC financing is being offered by tens of thousands of sellers already. 9. Learn how to acquire properties through buying debt, subject-to agreements, and loan assumptions. (Yes, they are still available when you know where to look).10. Discuss why today's prices (contrary to media mis-statements and err-prone commentators) are sure to increase substantially and how to identify the properties and locations that will experience the highest rates of appreciation.In addition to the above (and many other) revisions that are especially crafted to address the new opportunities and challenges that will exist for the next several.
years, this 7th edition will achieve elevated standards for clarity, application, and time-tested investment principles and practices (p&p which were often forgotten or ignored during the boom years)'--
Machine generated contents note: Prologue: Invest in Property Now Today's Odds Point Directly towards Present and Future Gains Develop and Execute Your Strategy Now Notes Chapter 1 Achieve a Prosperous Future: 22 Ways You Can Earn Profits with Property 1.1 Potential Sources of Profit from Investment Property 1.2 Is Property Your Best Investment Choice? Notes Chapter 2: OPM: Borrow Smart, Raise Cash, Build Equity 2.1 The Birth of'Nothing Down' 2.2 Should You Invest With Little or No Cash or Credit? 2.3 Maximize Leverage with Owner-Occupancy Financing 2.4 What Are the Loan Limits? 2.5 High Leverage for Investor-Owner Financing 2.6 How to Build Confidence with Lenders, Equity Investors, Sellers, and Sales Agents Notes Chapter 3: Appraisal: Ins and Outs of Market Value 3.1 What Is Market Value? 3.2 How to Estimate Market Value 3.3 Property Description 3.4 The Cost Approach 3.5 The Comparable Sales Approach 3.6 The GRM Income Approach 3.7 Income Capitalization 3.8 Valuation Methods: Summing Up Notes Chapter 4: Maximize Cash Flows And Grow Your Equity 4.1 Will the Property Yield Good Cash Flows? 4.2 Will the Property Yield Profitable Increases in Price? 4.3 Summing Up Chapter 5: Pay Less than Market Value 5.1 Why Properties Sell for Less (or More) than Market Value 5.2 Prepare Screening Criteria 5.3 Bargain Sellers 5.4 Seller Disclosures 5.5 Summary Chapter 6: Profit with Foreclosures 6.1 The Foreclosure Process 6.2 Buy Pre-Foreclosures from Distressed Owners 6.3 Prequalify Homeowners and Properties 6.4 Finding Homeowners in Default (Prefiling) 6.5 Find Homeowners (Post-Filing) 6.6 Satisfy Lenders and Lien Holders 6.7 Profit from the Foreclosure Auction 6.8 The Foreclosure Sale: Summing Up Chapter 7: Profit from REOs and Other Bargain Sales 7.1 Sad For Sellers/Builders, Bargains For You 7.2 How to Find REOs 7.3 HUD Homes and Other HUD Properties 7.4 Department of Veterans Affairs (REOs) 7.5 Fannie Mae and Freddie Mac REOs 7.6 Federal Government Auctions 7.7 Buy.
Keywords: Real estate investment -- United States